2007
DOI: 10.1126/science.1142358
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis Identifies Loci for Type 2 Diabetes and Triglyceride Levels

Abstract: New strategies for prevention and treatment of type 2 diabetes (T2D) require improved insight into disease etiology. We analyzed 386,731 common single-nucleotide polymorphisms (SNPs) in 1464 patients with T2D and 1467 matched controls, each characterized for measures of glucose metabolism, lipids, obesity, and blood pressure. With collaborators (FUSION and WTCCC/UKT2D), we identified and confirmed three loci associated with T2D-in a noncoding region near CDKN2A and CDKN2B, in an intron of IGF2BP2, and an intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

61
1,427
13
9

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,519 publications
(1,530 citation statements)
references
References 28 publications
61
1,427
13
9
Order By: Relevance
“…Especially, they were all located within CDKAL1 gene except for an intergenic variant of rs5015480 near HHEX gene. The association of the CDKAL1 gene concurred with the results from previous studies with American, 1 British, 5 French, 3 Danish, 4 Finnish, 2 Swedish, 1 Icelandic, 4 Korean, 9 Japanese, 10 and Chinese [11][12][13] populations. The significantly associated variants of the gene in the current study were specifically corresponding to those found in previous studies of Horikawa et al 14 and Wu et al 11 for rs7756992 and Zeggini et al 5 and Wu et al 11 for rs9465871 and rs10946398, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Especially, they were all located within CDKAL1 gene except for an intergenic variant of rs5015480 near HHEX gene. The association of the CDKAL1 gene concurred with the results from previous studies with American, 1 British, 5 French, 3 Danish, 4 Finnish, 2 Swedish, 1 Icelandic, 4 Korean, 9 Japanese, 10 and Chinese [11][12][13] populations. The significantly associated variants of the gene in the current study were specifically corresponding to those found in previous studies of Horikawa et al 14 and Wu et al 11 for rs7756992 and Zeggini et al 5 and Wu et al 11 for rs9465871 and rs10946398, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Especially, several genome-wide association studies were recently conducted. [1][2][3][4][5] Nevertheless, their results revealed inconsistencies in associations of many nucleotide sequence variants. 6 A serious publication bias was suspected because a fewer publications with negative results were likely to be reported from candidate gene association analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Recently many genome-wide association studies (GWAS) have been published on several complex diseases, such as type 2 diabetes (T2D) [Frazer et al, 2007;Saxena et al, 2007;Scott et al, 2007;Sladek et al, 2007;Steinthorsdottir et al, 2007;Zeggini et al, 2007]. Although these methods have been successful in finding new susceptibility genes for various complex diseases, not all the GWAS data are analyzed to their full potential.…”
Section: Introductionmentioning
confidence: 99%
“…Risk alleles refer to the type 2 diabetesassociated alleles, according to previous reports. [26][27][28][29][30][31][32][33] Multiple linear regression analyses were performed to test the independent effects of the risk alleles on BMI, VFA and SFA by taking into account the effects of other variables (i.e., age and gender) that were assumed to be independent of the effect of each SNP. The values of BMI, VFA and SFA were logarithmically transformed before multiple linear regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We selected 23 SNPs identified as susceptibility loci for type 2 diabetes by GWAS [26][27][28][29][30][31][32][33] and constructed Invader probes (Third Wave Technologies, Madison, WI, USA) for the following SNPs: notch 2 (NOTCH2) rs10923931, thyroid adenoma-associated (THADA) rs7578597, peroxisome proliferator-activated receptor g (PPARG) rs1801282, ADAM metallopeptidase with thrombospondin type 1 motif, 9 (ADAMTS9) rs4607103, insulinlike growth factor 2 mRNA-binding protein 2 (IGF2BP2) rs1470579, vascular endothelial growth factor A (VEGFA) rs9472138, JAZF zinc finger 1 (JAZF1) rs864745, cyclin-dependent kinase inhibitor 2A and cyclin-dependent kinase inhibitor 2B (CDKN2A/CDKN2B) rs564398 and rs10811661, hematopoietically expressed homeobox (HHEX) rs1111875 and rs5015480, transcription factor 7-like 2 (TCF7L2) rs7901695, potassium voltage-gated channel, KQT-like subfamily, member 1 (KCNQ1) rs2237892, potassium inwardly-rectifying channel, subfamily J, member 11 (KCNJ11) rs5215 and rs5219, exostosin 2 (EXT2) rs1113132, rs11037909, and rs3740878, melatonin receptor 1B (MTNR1B) rs10830963, dermcidin (DCD) rs1153188, tetraspanin 8/leucine-rich repeat containing G protein-coupled receptor 5 (TSPAN8/LGR5) rs7961581, and FTO rs8050136 and rs9939609. The SNPs were genotyped using Invader assays as previously described.…”
Section: Dna Extraction and Snp Genotypingmentioning
confidence: 99%